Mitral valve and tricuspid valve dysplasia in a 9‐week‐old Standardbred colt. (10th April 2012) - Duz, M.; Philbey, A. W.; Hughes, K. J.
Summary: A 9‐week‐old Standardbred colt was presented for investigation of dull demeanour, exercise intolerance and heart murmurs. Cardiac auscultation revealed a grade 5/6 holosystolic murmur and a grade 5/6 pansystolic murmur over the left and right cardiac apex respectively, and an irregularly irregular cardiac rhythm. Electrocardiographic examination findings were consistent with atrial fibrillation and tachycardia. Echocardiographic examination identified marked atrioventricular regurgitation and atrial dilation bilaterally, thickening of the mitral and tricuspid valves and dilation of the pulmonary artery consistent with pulmonary hypertension. No ventricular or atrial septal defect was present. Cardiomegaly and diffuse pulmonary oedema were evident on examination of lateral thoracic radiographs. Dysplasia of the mitral and tricuspid valves, eccentric cardiomegaly and pulmonary oedema were confirmed by post mortem examination. Dysplasia of the atrioventricular valves represents a rare cause of biventricular failure in the horse.